Prevalence, incidence and progression of lumbar spondylosis by gender and age strata. Issue 4 (July 2014) - Muraki, Shigeyuki; Yoshimura, Noriko; Akune, Toru; Tanaka, Sakae; Takahashi, Ikuno; Fujiwara, Saeko
Abstract Objectives. To identify the prevalence, incidence and progression of radiographic lumbar spondylosis (LS). Methods. From the Adult Health Study conducted by the Radiation Effects Research Foundation, 1, 204 participants aged 44–85 years who had lumbar spine radiographs in 1990–1992 were reexamined in 1998–2000 (mean 7.9-year interval). The radiographic severity of LS was determined by Kellgren/Lawrence (KL) grading. Results. In the overall population, the prevalence of radiographic KL ≥ 2 and ≥ 3 LS was 52.9% and 23.6%, respectively. KL ≥ 2 LS was more prevalent in men, whereas KL ≥ 3 LS was more prevalent in women. During the 8-year follow-up, the incidence of KL ≥ 2 LS in men and women was 65.5% and 46.6%, that of KL ≥ 3 LS was 27.3% and 29.5%, that of progressive LS was 31.3% and 34.0%, and multilevel LS was 44.9% and 33.4%, respectively. Body–mass index was a risk factor for both KL ≥ 2 and KL ≥ 3 LS, after adjusting for age and sex. Conclusions. The present longitudinal study revealed the prevalence, incidence and progression of radiographic LS. Prevalence and incidence of KL ≥ 2 LS was higher in men than women, while, those of KL ≥ 3 were similar between men and women.